Answer:
c=-5
d=1
Step-by-step explanation:
[tex](cy^2)(4y^d)=-20y^3[/tex]
I'm going to reorder the left-hand side. Multiplication is commutative.
[tex](4c)(y^2y^d)=-20y^3[/tex]
Since the bases are the same in [tex]y^2y^d[/tex] and the operation is multiplication, I'm going to add the exponents giving me:
[tex]4cy^{2+d}=-20y^3[/tex]
So this implies we have two equations to solve:
[tex]4c=-20[/tex] and [tex]2+d=3[/tex]
So the first equation can be solved by dividing both sides by 4 giving you [tex]c=-5[/tex].
The second equation can be solved by subtracting 2 on both sides giving you [tex]d=1[/tex].